Functional outcomes of pre-hospital thrombolysis in a mobile stroke treatment unit compared with conventional care: an observational registry study. Issue 10 (September 2016) - Kunz, Alexander; Ebinger, Martin; Geisler, Frederik; Rozanski, Michal; Waldschmidt, Carolin; Weber, Joachim E; Wendt, Matthias; Winter, Benjamin; Zieschang, Katja; Fiebach, Jochen B; Villringer, Kersten; Erdur, Hebun; et al.
Summary: Background: Specialised CT-equipped mobile stroke treatment units shorten time to intravenous thrombolysis in acute ischaemic stroke by starting treatment before hospital admission; however, direct effects of pre-hospital thrombolysis on clinical outcomes have not been shown. We aimed to compare 3-month functional outcomes after intravenous thrombolysis in patients with acute ischaemic who had received emergency mobile care or and conventional care. Methods: In this observational registry study, patients with ischaemic stroke received intravenous thrombolysis (alteplase) either within a stroke emergency mobile (STEMO) vehicle (pre-hospital care covering 1·3 million inhabitants of Berlin) or within conventional care (normal ambulances and in-hospital care at the Charité Campus Benjamin Franklin in Berlin). Patient data on treatment, outcome, and demographics were documented in STEMO (pre-hospital) or conventional care (in-hospital) registries. The primary outcome was the proportion of patients who had lived at home without assistance before stroke and had a 3-month modified Rankin Scale (mRS) score of 1 or lower. Our multivariable logistic regression was adjusted for demographics, comorbidities, and stroke severity. This study is registered withClinicalTrials.gov, numberNCT02358772 . Findings: Between Feb 5, 2011, and March 5, 2015, 427 patients were treated within the STEMO vehicle and their data were entered into a pre-hospital registry. 505 patients received conventional care and their data were entered into an in-hospital thrombolysis registry. Of these, 305 patients in the STEMO group and 353 in the conventional care group met inclusion criteria and were included in the analysis. 161 (53%) patients in the STEMO group versus 166 (47%) in the conventional care group had an mRS score of 1 or lower (p=0·14). Compared with conventional care, adjusted odds ratios (ORs) for STEMO care for the primary outcome (OR 1·40, 95% CI 1·00–1·97; p=0·052) were not significant. Intracranial haemorrhage (p=0·27) and 7-day mortality (p=0·23) did not differ significantly between treatment groups. Interpretation: We found no significant difference between the proportion of patients with a mRS score of 1 or lower receiving STEMO care compared with conventional care. However, our results suggest that pre-hospital start of intravenous thrombolysis might lead to improved functional outcome in patients. This evidence requires substantiation in future large-scale trials. Funding: Zukunftsfonds Berlin, the Technology Foundation Berlin with EU co-financing by the European Regional Development Fund via Investitionsbank Berlin, and the German Federal Ministry for Education and Research via the Center for Stroke Research Berlin.